Sphenoidal fontanelle area measurement on rendered three-dimensional ultrasound. - Ioannou, C; Sarris, I; Javaid, M; Papageorghiou, A (2012)
OBJECTIVE: Rendered three-dimensional images of the fetal cranial vault permit the identification of sutures and measurement of the fontanelle surface area. The objective of this study was to establish the feasibility and repeatability of sphenoidal fontanelle area measurement. METHOD: Head volumes were obtained using the biparietal diameter as the reference plane. These were displayed with maximum rendering and the surface area of the sphenoidal fontanelle was measured by one operator. Feasibility was expressed as the percentage of scans with a successful measurement at different gestational ages. Repeatability was expressed as coefficient of variation (CV), intraclass correlation coefficient (ICC) and Bland-Altman plots. RESULTS: Thirty women underwent 141 scans. Feasibility of sphenoidal fontanelle measurement is over 90% before 26 weeks, but drops gradually thereafter and becomes 0% at 34 weeks. Intraobserver repeatability of measurement on the same scan image demonstrated CV = 17.5% and ICC = 0.883; however, when measuring a newly acquired volume, the repeatability is poor, CV = 30.7% and ICC = 0.649. CONCLUSION: Although it is feasible to visualize the sphenoidal fontanelle on rendered three dimensions, its surface area measurement is not reliable for clinical use. There is potential to overestimate repeatability when remeasuring the same volume.